Structural knowledge: how executive experience with structural composition affects intrafirm mobility and unit reconfiguration - Karim, Samina; Williams, Charles (Strategic Management Journal, 2012)
This article explores how knowledge embodied in executives is tied to the organizational context in which it develops. Drawing on the knowledge‐based view of the firm and human capital theory, we predict that executives will move between units with similar ‘structural composition’—a characteristic representing unit origin (as acquired or internally developed) and how the unit was reconfigured. We further argue that executives will be conduits of organizational change. We predict that units receiving more transferred executives, executives with recombination experience, and executives from core internal units will have a greater likelihood of being recombined, while units receiving executives from previously acquired units will tend to remain unchanged. The study examines a 20‐year panel of 48 multidivisional firms from the U.S. medical sector. Copyright © 2012 John Wiley & Sons, Ltd.